The bond behaviour of CFRP-to-steel bonded joints with varying bond properties at elevated temperatures. (15th March 2019) - Zhou, Hao; Torres, Juan P.; Fernando, Dilum; Law, Angus; Emberley, Richard
Highlights: Effect of varying bond-slip relation on the behaviour of CFRP-to-steel bonded joints under sustained load is studied. Effect of the bond length on the bond behaviour of CFRP-to-steel joints with varying bond-slip relations. Effect of the mechanical loading rate to thermal loading rate on the bond behaviour of CFRP-to-steel bonded joints is investigated. Abstract: The mechanical properties of different adhesives at elevated temperatures can change differently due to the differences in adhesive molecular chain structure. Therefore, a profound understanding of the effect of these property changes on the bond behaviour of carbon fibre reinforced polymer (CFRP)-to-steel bonded joints is of great importance when designing bonded CFRP strengthening systems for steel structures. Existing studies on CFRP-to-steel bonded joints under monotonic loading have clearly shown that both adhesive mechanical properties and geometrical properties of the bonded joints (e.g. bond length) may significantly influence the bond strength. Existing studies on adhesive mechanical properties under elevated temperatures have shown that the variation of adhesive mechanical properties, especially fracture energy with temperature depends significantly on the adhesive type. No comprehensive study exists so far on understanding the effects of key mechanical and geometrical parameters of a CFRP-to-steel bonded joints at elevated temperatures on bond strength. This paper presents a study aimed at understanding the effects of different parameters such as temperature dependent mechanical properties of adhesive and bond length on the behaviour of CFRP-to-steel bonded joints at elevated temperatures. Results of this study showed that (1) load-displacement behaviour of the bonded joints is sensitive to temperature variations, (2) for bonded joints with sufficiently long bond length, the ultimate load depends only on the fracture energy of the final temperature, and (3) the maximum load of the bonded joints depends on the ratio between the loading and heating rates.